Effectiveness of an Educational Program on Nursing Staff Knowledge towards Priorities of Responsibilities at Emergency Unit in Imam Al-Hussein Medical City in Holly Karballah Governorate (Indian Journal of Forensic Medicine & Toxicology, 2021)
The study aims to determine the effectiveness of an education program on nursing staff knowledge toward priorities of responsibilities and to identify the association between nursing staff knowledge and demographic characteristics of (age, gender, education level and year of experiences). A pre-experimental design (one group pre-test –post-test design) has been used. The study has been carried out at Emergency Unit in Imam Al-Hussein Medical City in Holly Karballah Governorate at the period from (26th of September, 2020 to 18th of April, 2021) on a non-probability (purposive) sample consisting of (28 nurses) who work in the emergency unit . A questionnaire was built as a data collection tool and consisted of two parts: First part: The demographic characteristics of the nursing staff (age, gender, level of education, years of experience in hospital, years of experience in emergency and level of education, and second part includes : Knowledge of Nursing Staff about Priorities of Responsibilities at Emergency Unit ,and consist of four domain. The validity of content of program and the study instruments were determined through a panel of (11) experts. The data analyzed by using Statistical Package for Social Sciences (SPSS) version 25 application of statistical analysis system .The study findings revealed that nursing staffs’ knowledge regards Priorities of Responsibilities at Emergency Unit before application of the program was poor with a statistical mean equal to( 1.28) and after implementing the educational program became good with a statistical mean equal to (1.78). The study show that there is a positive effect of the educational program on the nursing staff’s knowledge, where p-value was (0.000) in two periods of measurements (pre-test and post-test). The study recommended the necessity of improving the knowledge of the nursing staff regarding the priorities of their responsibilities in the emergency unit by the activation of continuing medical education in correctly .
Keywords: Educational program, Nursing staffs’ Knowledge, Priorities of Responsibilities, Emergency Nurses, Emergency Unit